Perancangan Sistem Penggajian Web yang Terintegrasi di PT Hong Xin Printing Equipment - Kevin Kevin; Prya Artha Widjaja (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
PT Hong Xin Printing Equipment is encountering obstacles in improving operational efficiency and managing human resources in the digital age. Despite the use of a fingerprint attendance system, there are concerns about errors and reduced efficiency due to manual data processing. Additional challenges arise when recording attendance for employees on business trips and manually calculating leave. To tackle these issues, the company is planning to create a web-based payroll system that will automate payroll, attendance, and leave management. The implementation of this system is anticipated to enhance efficiency and accuracy, thereby allowing the company to maintain its competitiveness in the market.